Inside the atom - Asimov, Isaac, 1920- (New York : Abelard-Schuman, 1974)
Discusses in detail the structure and behavior of the atom and its present and future uses, especially in light of the world's energy crisis.
A ladder edition at the 2,000-word level adapted by Herzl Fife.
Keywords: Nuclear energy -- Popular works; Atoms